Semimetal–dielectric–metal metasurface for infrared camouflage with high-performance energy dissipation in non-atmospheric transparency window - Zhou Dongjie; Zhang Jinguo; Tan Chong; Li Liyan; Qiu Qianli; Zhang Zongkun; Sun Yan; Zhou Lei; Dai Ning; Chu Junhao; Hao Jiaming (Nanophotonics)
The development of novel camouflage technologies is of great significance, exerting an impact on both fundamental science and diverse military and civilian applications. Effective camouflage aims to reduce the recognizability of an object, making it to effortlessly blend with the environment. For infrared camouflage, it necessitates precise control over surface emissivity and temperature to ensure that the target blends effectively with the surrounding infrared background. This study presents a semimetal–dielectric–metal metasurface emitter engineered for the application of infrared camouflage. The metasurface, with a total thickness of only 545 nm, consists of a Bi micro-disk array and a continuous ZnS and Ti film beneath it. Unlike conventional metal-based metasurface design, our approach leverages the unique optical properties of Bi, achieving an average emissivity of 0.91 in the 5–8 μm non-atmospheric transparency window. Experimental results indicate that the metasurface emitter achieves lower radiation and actual temperatures compared to those observed in comparative experiments, highlighting its superior energy dissipation and thermal stability. The metasurface offers advantages such as structural simplicity, cost-effectiveness, angular insensitivity, and deep-subwavelength features, rendering it suitable for a range of applications including military camouflage and anti-counterfeiting, with potential for broad deployment in infrared technologies.